Genetic variation and association between seedling root traits and yield in chickpea (Cicer Arietinum L.) - Kumar, Amit; Kumar, Hitesh; Kumar, Mukul; Gupta, Vikas; Kumar, Arun; Singh, Vivek (Bangladesh Journal of Botany, 2023)
In the present study, 90 chickpea germplasm lines for yield and related traits, along with early plant growth root system architecture traits, under controlled conditions after 25, 30, and 35 days of sowing were evaluated. The analysis of variance revealed significant variation in traits such as shoot length, secondary root branches, days to 50 % flowering, days to maturity, seed index, plant height, and seed yield. Additionally, primary root length was positively correlated with shoot length and the number of root branches at all three seedling growth stages. The findings suggest that early shoot length and seedling root length, particularly more secondary root branches, are crucial traits that should be incorporated into chickpea breeding programs to develop new elite cultivars with improved yield potential, better resistance to biotic and abiotic stresses, and enhanced crop productivity. Bangladesh J. Bot. 52(3): 791-797, 2023 (September)